THE IMPACT OF LOCAL TAXES, LOCAL FEES, AND TKKD ON THE REVENUE OF BANTEN PROVINCE - Yusenda Ragil Saputri; Ruth Eviana Hutabarat (MESP–FEB UNS, 2026)
This study aims to analyze the structural contribution of local taxes, local levies, and Transfers to Regions and Village Funds (TKKD) in forming regional revenue in Banten Province for the period 2016–2024. This study uses secondary data from the Budget Realization Report (LRA) of districts/cities in Banten Province over nine years of observation, resulting in 72 panel data observations. The analysis method used is panel data regression with a Fixed Effect Model. The results indicate that local taxes, local levies, and TKKD each make a positive and significant contribution to regional revenue. Comparatively, local levies have the largest coefficient (2.4213116), followed by local taxes (1.389492) and TKKD (0.4124826). The R-squared value of 0.7339 indicates that the independent variables explain 73.39% of the variation in regional revenue. Given that the independent variables are structural components of regional revenue, the estimates reflect fiscal sensitivity rather than pure causal relationships. This finding indicates that even though Local Own-Source Revenue capacity has increased, fiscal dependence on central government transfers remains considerable. This study contributes by integrating the TKKD variable into provincial-level panel data analysis and presenting the latest empirical evidence on the structure of regional fiscal dependence in Banten Province. The policy implications emphasize the importance of optimizing local tax and levy collection and strengthening fiscal independence to reduce the dominance of central transfers in the regional revenue structure.